Impaired Lysosome Reformation in Chloroquine-Treated Retinal Pigment Epithelial Cells - Cardoso, M. Helena (2023)
Purpose: To model the in vivo effects of chloroquine on the retinal pigment epithelium in experimentally tractable cell culture systems and determine the effects of mild chloroquine treatment on lysosome function and turnover. Methods: Effects of low-dose chloroquine treatment on lysosomal function and accessibility to newly endocytosed cargo were investigated in primary and embryonic stem cell-derived RPE cells and ARPE19 cells using fluorescence and electron microscopy of fluorescent and gold-labeled probes. Lysosomal protein expression and accumulation were measured by quantitative PCR and Western blotting. Results: Initial chloroquine-induced lysosome neutralization was followed by partial recovery, lysosomal expansion, and accumulation of undegraded endocytic, phagocytic, and autophagic cargo and inhibition of cathepsin D processing. Accumulation of enlarged lysosomes was accompanied by a gradual loss of accessibility of these structures to the endocytic pathway, implying impaired lysosome reformation. Chloroquine-induced accumulation of pro-cathepsin D, as well as the lysosomal membrane protein, LAMP1, was reproduced by treatment with protease inhibitors and preceded changes in lysosomal gene expression. Conclusions: Low-dose chloroquine treatment inhibits lysosome reformation, causing a gradual depletion of lysosomes able to interact with cargo-carrying vacuoles and degrade their content. The resulting accumulation of newly synthesized pro-cathepsin D and LAMP1 reflects inhibition of normal turnover of lysosomal constituents and possibly lysosomes themselves. A better understanding of the mechanisms underlying lysosome reformation may reveal new targets for the treatment of chloroquine-induced retinopathy.